On the Hypothetical Iberolux (Comillas Journal of International Relations, 2022)
The first decades of the 19th century were very damaging for the Iberian economies. In short, the Napoleonic occupations in Spain and Portugal led to the expulsion of their respective monarchs, while many of the Spanish and Portuguese colonies took advantage of it, to gain independence and become independent states. Consequently, revenues fell drastically, because part of the traditional market for some peninsular products was lost. In this context, it seems reasonable that given the advantages of the German Zollverein, a substitute for the Iberian Peninsula was intended. However, no consensus was reached. Later, in 1986, with the simultaneous incorporation of Spain and Portugal to the European Economic Community, greater Iberian cooperation was promoted. Fortunately, Spain and Portugal share economic agreements that make them preferred partners. While it is true, the referred Iberian cooperation could be optimized, taking the Benelux as an example, which in our case would be called Iberolux.
Keywords: trade agreements; tariff abolition; Iberian cooperation